P251 Tuberculosis in older versus younger adult patients: a retrospective comparison of patient characteristics and treatment outcomes at a major UK referral centre. (12th November 2015) - Abbara, A; Buell, KG; Sullivan, JAL; Collin, SM; Kon, OM; Hansel, T; John, L; Davidson, RN
Abstract : Introduction and objectives: Tuberculosis (TB) in older persons presents challenges related to diagnosis, management, comorbidities and polypharmacy potentially contributing to increased morbidity and mortality. This retrospective cohort review compares the baseline characteristics, diagnosis, management and outcome between older patients (OPs) (over 65 years) and younger patients (YPs) (25–35 years.) Method: All patients ≥65 years treated at Northwick Park Hospital during 2002–2014 were identified from London TB register; a comparison group of patients aged 25–35 years were randomly selected. Clinical, microbiological, radiological and biochemical parameters together with management and outcomes were obtained from electronic records. Characteristics of patients were compared between the two groups using Chi-squared and Kruskal-Wallis tests; analyses were performed using Stata (Stata Corp. 2013). Results: The comparison groups comprised 313 patients aged ≥65 years and 339 patients aged 25–35. Demographics, site of disease, TB culture, treatment regimens and outcomes are recorded in Table 1 . 35.6% of OPs and 29.6% of YPs were symptomatic for >2 months at review in secondary care. Median duration to starting treatment from review was 17 days (IQR: 4–57) in OPs compared to 2 (IQR: 1–19) in YPs (p = 0.001). 44.8% of OPs experienced drug toxicity compared to 27.3% of YPs (p = <0.001.) Gastrointestinal symptoms affected 24.8% and 9.6% of OPs and YPs respectively (p < 0.001). There was no difference in prevalence of rash (4.8% in OPs, ) arthralgia (2.4% of OPs, ) or drug induced liver injury (6.4% of OPs, p = 0.32.) Comorbidities were higher in OPs, with diabetes present in 34.5%, hypertension in 52.6% and renal failure in 17.9% compared to 1.5%, 1.2% and 1.8% in YPs (all p = 0.001). 58.8% of ≥65 and 37.9% of YPs had inpatient admissions, with 30% of OPs admitted for >10 days (p = <0.001). Completion was 78.7% and mortality 16.0% amongst OPs, versus 91.2% with no deaths amongst YPs (both p = <0.001). Conclusion: These data characterise the delays in presentation and treatment initiation in older patients who also experience a more complicated treatment course with an increased side effect profile, more variation from standard quadruple therapy, lower completion rates and poorer outcomes. This, together with longer inpatient stays impacts patients, but also has financial implications for services.